Analisis Penerimaan Aplikasi Alfagift Di Kota Surabaya Menggunakan Metode Technology Acceptance Model - Hanifa, Fatya; Putri, Callista Harnit; F.N, Aryananda; Wulansari, Anita (Jurnal Sains dan Teknologi (JSIT), 2023)
This research aims to determine how the acceptance of the Alfagift application, is measured using the Technology Acceptance Model (TAM) method. The variables that will be analyzed are Perceived Ease of Use (PEU), Perceived Usefulness (PU), Behavioral Intention to Use (BIU), Actual Usage Behavior (AU), and Attitude Toward Using (ATU). The target respondents are residents of Surabaya who have used the Alfagift application to purchase household necessities. We collected samples by distributing research questionnaires. Subsequently, we conducted tests for validity, reliability, and multiple linear regression. The findings of our research are as follows: 1) PEU has a positive and significant impact on PU; 2) PEU has a positive and significant impact on ATU; 3) PU has a positive and significant impact on ATU; 4) ATU has a positive and significant impact on BIU; 5) BIU has a positive and significant impact on AU.